Experts as sources in reported agricultural articles in Nigerian dailies (2010)
Agricultural stories are routinely reported in daily newspapers in Nigeria. Few studies have however provided empirical evidence that experts were contacted for comments in reported agricultural stories. In this study, four major Nigerian daily newspapers were content analysed to determine if experts were contacted for comments in the coverage of agricultural stories over a five-year time frame -from January 1through December 31, 2004. Findings reveal a continuous coverage of agricultural stories with a majority (25%) reported in 2001. Coverage of agricultural stories was highest (31.6%) in the Guardian newspaper. The study identified that expert comments were relied upon by all daily newspapers for all reported agricultural stories within the time frame of the study. Although, fluctuations were observed, findings suggest increase in use of experts comments in reported agricultural stories, as all the newspapers routinely contacted experts for comments in all the years investigated. Overall, it is suggested that Nigerian daily newspapers sustain this trend, and increase the frequency of their agricultural contents.